Sensitivitas Pedagogis Guru Sekolah Dasar - Mahatma Mahatma (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Teaching can be a complex endeavor. Every time teaching always innumerable questions arise in a teacher. This shows that the teacher's pedagogical sensitivity is beginning to erode. Teachers are no longer accustomed to discussing various pedagogical aspects, such as how to interact with students on a relational, personal and moral basis. Teachers also have difficulty discussing pedagogical issues with students' parents. This qualitative research was conducted in Jakarta in 2022. The research sample came from 19 elementary school teachers. The findings show the importance for teachers to build and develop sensitivity and pedagogical language in everyday learning activities.